Role of Interleukin-6 in Vascular Health and Disease - Villar-Fincheira, Paulina; Sanhueza-Olivares, Fernanda; Norambuena-Soto, Ignacio; Cancino-Arenas, Nicole; Hernandez-Vargas, Felipe; Troncoso, Rodrigo; Gabrielli, Luigi; Chiong, Mario (Frontiers in Molecular Biosciences, 2021)
IL-6 is usually described as a pleiotropic cytokine produced in response to tissue injury or infection. As a pro-inflammatory cytokine, IL-6 activates innate and adaptative immune responses. IL-6 is released in the innate immune response by leukocytes as well as stromal cells upon pattern recognition receptor activation. IL-6 then recruits immune cells and triggers B and T cell response. Dysregulated IL-6 activity is associated with pathologies involving chronic inflammation and autoimmunity, including atherosclerosis. However, IL-6 is also produced and released under beneficial conditions, such as exercise, where IL-6 is associated with the anti-inflammatory and metabolic effects coupled with physical adaptation to intense training. Exercise-associated IL-6 acts on adipose tissue to induce lipogenesis and on arteries to induce adaptative vascular remodeling. These divergent actions could be explained by complex signaling networks. Classical IL-6 signaling involves a membrane-bound IL-6 receptor and glycoprotein 130 (gp130), while trans-signaling relies on a soluble version of IL-6R (sIL 6R) and membrane-bound gp130. Trans-signaling, but not the classical pathway, is regulated by soluble gp130. In this review, we discuss the similarities and differences in IL-6 cytokine and myokine signaling to explain the differential and opposite effects of this protein during inflammation and exercise, with a special focus on the vascular system.